2014
DOI: 10.1155/2014/798170
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Microtubule-Associated Protein MAP9/ASAP and Its Partners AURKA and PLK1 in Colorectal and Breast Cancers

Abstract: Background. Colorectal and breast cancers are among the most common cancers worldwide. They result from a conjugated deficiency of gene maintenance and cell cycle control. Objective. We investigate the expression of the microtubule-associated protein MAP9/ASAP and its two partners AURKA and PLK1 in colorectal tumors as well as in ductal breast cancers. Materials and Methods. 26 colorectal cancer samples and adjacent normal tissues and 77 ductal breast cancer samples from grade I to grade III were collected. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…MAP9 (microtubule-associated protein 9; also known as ASAP) is a microtubule-associated protein required for spindle function, mitotic progression, and cytokinesis (32). Expression of MAP9 is downregulated in colorectal cancer compared to normal tissues (33). RSPH9 (radial spoke head 9 homolog) encodes a protein thought to be a component of the radial spoke head in motile cilia and flagella.…”
Section: Discussionmentioning
confidence: 99%
“…MAP9 (microtubule-associated protein 9; also known as ASAP) is a microtubule-associated protein required for spindle function, mitotic progression, and cytokinesis (32). Expression of MAP9 is downregulated in colorectal cancer compared to normal tissues (33). RSPH9 (radial spoke head 9 homolog) encodes a protein thought to be a component of the radial spoke head in motile cilia and flagella.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells, MAP9 decorates the mitotic spindle and overexpression causes monopolar spindles, while knockdown leads to multipolar spindles and defects in cytokinesis (Saffin et al, ). MAP9 is also down‐regulated in certain types of cancers, such as colorectal cancer, and could be used as a valuable disease marker (Rouquier et al, ). These findings indicate that MAP9 has a crucial role in the organization of the bipolar mitotic spindle and in mitotic progression.…”
Section: Introductionmentioning
confidence: 99%
“…MAP9 is phosphorylated by Aurora kinase A (AURKA) and polo-like kinase 1 (Plk1) during cell mitosis and is essential for spindle assembly, centrosome regulation, and cell division (Saffin et al, 2005;Venoux et al, 2008). The expression of MAP9 is downregulated in colorectal cancer, whereas AURKA and Plk1 are upregulated (Rouquier et al, 2014). Dysregulation of AURKA and Plk1 are strongly associated with tumorigenesis (Weng Ng et al, 2016;Al-Khafaji et al, 2017;Chen et al, 2017;Zhu et al, 2017), and AURKA polymorphisms have also been reported in association with GC and breast cancer (Lopez-Cortes et al, 2018;Mesic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%